Presenting a Model for Setting in Narrative Fiction Illustration - Namin, Hajar Salimi (Journal of History Culture and Art Research, 2017)
The present research aims at presenting a model for evaluating and enhancing training the setting in illustration for narrative fictions for undergraduate students of graphic design who are weak in setting. The research utilized expert’s opinions through a survey. The designed model was submitted to eight experts, and their opinions were used to have the model adjusted and improved. Used as research instruments were notes, materials in text books, papers, and related websites, as well as questionnaires. Results indicated that, for evaluating and enhancing the level of training the setting in illustration for narrative fiction to students, one needs to extract sub-indexes of setting. Moreover, definition and recognition of the model of setting helps undergraduate students of graphic design enhance the level of setting in their works skill by recognizing details of setting. Accordingly, it is recommended to design training packages to enhance these sub-indexes and hence improve the setting for narrative fiction illustration.